Effects of heat treatment on corrosion fatigue and stress corrosion crack growth of additive-manufactured Alloy 800H in high-temperature water. (October 2021) - Yang, Jingfan; Song, Miao; Hawkins, Laura R.; Liu, Xiang; He, Lingfeng; Lou, Xiaoyuan
Highlights: Carbide formation and sensitization in stress-relieved and sensitized AM 800H. Grain inhomogeneity and high twin fraction in recrystallized AM 800H. Heat treatment less affected corrosion fatigue crack growth under cyclic loading. SCC of AM 800H is sensitive to carbides, grain inhomogeneity, twins, sensitization. AM 800H needs to be used with caution even after HIP, due to its inconsistent cracking behaviour. Abstract: Crack growth behaviour of additively manufactured (AM) Alloy 800H were studied under cyclic and static load in high-temperature water, focusing on heat treatment effects. Under cyclic loading, heat treatment gently affected corrosion fatigue. The growth rate is comparable to wrought 800H. As the load cycle frequency reduced to below 0.001 Hz, AM 800H exhibited inconsistent stress corrosion cracking response as compared to wrought 800H. Depending on heat treatment, inhomogeneous crack propagation and localized pinning were observed in stress-relieved and recrystallized AM 800H, attributed to carbides, microstructural inhomogeneity, and twin boundaries. Grain boundary sensitization at ˜10 wt% Cr caused fast crack growth.